Effect of bisphosphonate treatment of titanium surfaces on alkaline phosphatase activity in osteoblasts: a systematic review and meta-analysis - Christian Wehner; Stefan Lettner; Andreas Moritz; Oleh Andrukhov; Xiaohui Rausch-Fan (BMC, 2020)
Abstract Background Bisphosphonate coating of dental implants is a promising tool for surface modification aiming to improve the osseointegration process and clinical outcome. The biological effects of bisphosphonates are thought to be mainly associated with osteoclasts inhibition, whereas their effects on osteoblast function are unclear. A potential of bisphosphonate coated surfaces to stimulate osteoblast differentiation was investigated by several in vitro studies with contradictory results. The purpose of this systematic review and meta-analysis was to evaluate the effect of bisphosphonate coated implant surfaces on alkaline phosphatase activity in osteoblasts. Methods In vitro studies that assessed alkaline phosphatase activity in osteoblasts following cell culture on bisphosphonate coated titanium surfaces were searched in electronic databases PubMed/MEDLINE, Scopus and ISI Web of Science. Animal studies and clinical trials were excluded. The literature search was restricted to articles written in English and published up to August 2019. Publication bias was assessed by the construction of funnel plots. Results Eleven studies met the inclusion criteria. Meta-analysis showed that coating of titanium surfaces with bisphosphonates increases alkaline phosphatase activity in osteoblasts after 3 days (n = 1), 7 (n = 7), 14 (n = 6) and 21 (n = 3) days. (7 days beta coefficient = 1.363, p-value = 0.001; 14 days beta coefficient = 1.325, p-value < 0.001; 21 days beta coefficient = 1.152, p-value = 0.159). Conclusions The meta-analysis suggests that bisphosphonate coatings of titanium implant surfaces may have beneficial effects on osteogenic behaviour of osteoblasts grown on titanium surfaces in vitro. Further studies are required to assess to which extent bisphosphonates coating might improve osseointegration in clinical situations.